Effects of Complementary Alternative Medicine on Hyperemesis Gravidarum: A Systematic Review - Finta Isti Kundarti; Ira Titisari; Dwi Estuning Rahayu (Journal of Health Technology Assessment in Midwifery, 2023)
Background: Nausea and vomiting of pregnancy (NVP) is a common problem for pregnant women. Many pregnant women are worried about the side effects of pharmacological therapy, thus encouraging them to use non-pharmacological therapy. Researchers have recently paid particular attention to complementary medicine methods for the treatment of NVP. With regard to the high prevalence of NVP as well as the adverse effects of chemicals on the mother and fetus of the drug, this study focused on assessing the safety and efficacy of different non-pharmacological methods in eliminating NVP. This systematic review was carried out to assess the safety and efficacy of different non-pharmacological methods in eliminating NVP. Methods: This study used a systematic review method by conducting a literature search through the PubMed database, Cochrane library, Science direct, Proquest, and Google Scholar with publication years starting January 2011 and January 2021. Results: A total of ten articles were selected as part of the final sample according to the inclusion criteria. Of the 10 articles, 2 were about the use of ginger, 3 were about Acupuncture-moxibustion, 2 were about psychotherapy, one was about Progressive muscle relaxation, and 2 were about psychoeducation. Studies have shown a positive effect on NVP reduction; however, no side effects were reported. Conclusion: According to the results of this review, most of the methods used are effective in reducing the incidence of NVP, among which ginger and P6 acupressure can be recommended more reliably.